Reformas necesarias al código penal ecuatoriano en cuanto a las nuevas figuras delictivas que atentan contra el derecho a la vida - Cartagena Valencia, Clever Javier (2012)
With the present investigation work, I seek to give to know the readers that the topic of the insecurity in our country has become a strong social problem that should be analyzed and studied in all its structure and magnitude by all the components of the State, in order to look for solutions and procedures to short, medium and I release term and this way to be able to brake the big criminal indexes that register in the newspaper to live off our society. Without a doubt the material object is no longer constituted in the only end of the delinquency that is in risk, but rather also the juridical object that is the Life or the Physical Integrity of people is in permanent risk; it is for that reason that I believe necessary that should be studied it to this social problem and to understand it so much as a problem of supreme importance at level of State as at society level since has been evidenced in the last years to parecimiento of new criminal figures related to the Organized Crime, Sicariato, Social Cleaning and Vendetta that have unchained a great index of violent deaths generating a great imbalance and social shock in most of the Ecuadorian population. In the country it is increasing the rates of mortality considerably by reason of these new criminal behaviors, this makes meditate on the level of violence implanted in our society; using diverse types of criminal activities as mechanism to solve conflicts of personal character in the diverse strata, scenarios and relationships of the society. Their persistence and intensity have granted him certain normality even considering that we are getting used to live inside a violent order, that is to say the relationship forms characterized essentially by mechanisms of force, coercion and fear being imposed. With this work it is not sought to insinuate that in the country it is the violence the only interaction form among people, individuals and institutions, it is rather to give to know that the violent actions are taking acceptance on all the other forms possible of human relationship. It is necessary to give to know that in the last decade, an increment of the violence has been noticed generalized in all the social levels; the alteration of values where each individual is worth for what has and not for what is where the end justifies the means, reigning the law of the strongest, he/she makes that the new generations are formed a concept wandered about that that in fact means a worthy Life where the values like the respect, the peace, the solidarity, the understanding, the acceptance, they are being ignored in our society. Then I define as a juridical-social and fundamental problem to these new criminal behaviors that you/they have appeared lately they are due to that are not tipificadas or properly sanctioned by our penal legislation This impunity for lack of a normative one artificial that doesn't allow to investigate and worse still to sanction to the authors accomplices and concealing that make these new crimes, it has motivated the reason of being of this investigation. For all him before suitable the necessity exists of adopting conducive measures to carry out an artificial reformation to our Penal Code that allows the criminalization and legalization of these new crimes, so that the dispositions of our Constitution of the Republic and of the International Treaties they allow to conserve, to respect and to guarantee the inalienable right to the Life that all the people have with the simple one made of to live or to reside in this territory.